Analisis Kualitas Bakteriologis Air Minum dan Tindakan Ibu dengan Kejadian Diare pada Balita - Alifatu Rosyida Yuri; Aliefiyah Naimatul Azizah; Ahmad Rido'i Yuda Prayogi; Retrno Adriyani (Jurnal Kesehatan Manarang, 2022)
Diarrhea in children under five is one of the health problems in Indonesia with 21 of outbreak with a total of 1,725 ​​cases and 34 deaths with a Case Fatality Rate (CFR) of 1.97%. Springs are one of the sources of drinking water that are widely used by the community with 1.8 billion people still using sources that are contaminated with faeces. Objective to analyze the bacteriological quality of drinking water sourced from springs and the actions of mothers with the incidence of diarrhea in children under five in Paspan Village, Glagah District, Banyuwangi. This type of research is a quantitative research with a cross sectional study design. The population in this study were 47 housewives who had toddlers in Paspan Village. This study consisted of 3 samples, namely 1 sample of clean water managed by community, 28 samples of respondent's drinking water and housewives who have toddlers using simple random sampling method. The result of study showed that 75% of the bacteriological quality of drinking water had met the requirements and 53.6% of the mother's actions were in the bad category. A total of 7.1% of children under five in Paspan Village experienced diarrhea. Bacteriological quality of drinking water sourced from springs (p = 0.056) and maternal actions (p = 0.040). There is no relationship between bacteriological quality and the incidence of diarrhea in children under fiveHowever, there is a relationship between maternal actions and the incidence of diarrhea in children under five in Paspan Village, Glagah District, Banyuwangi.